Pharmacological Preconditioning with GYKI 52466: A Prophylactic Approach to Neuroprotection - Goulton, Chelsea S.; Patten, Anna R.; Kerr, John R.; Kerr, Steve (Frontiers in Neuroscience, 2010)
Some toxins and drugs can trigger lasting neuroprotective mechanisms that enable neurons to resist a subsequent severe insult. This ‘pharmacological preconditioning’ has far-reaching implications for conditions in which blood flow to the brain is interrupted. We have previously shown that in vitro preconditioning with the AMPA receptor antagonist GYKI 52466 induces tolerance to kainic acid (KA) toxicity in hippocampus. This effect persists well after washout of the drug and may be mediated via inverse agonism of G protein linked receptors. Given the amplifying nature of metabotropic modulation, we hypothesised that GYKI 52466 may be effective in reducing seizure severity at doses well below those normally associated with adverse side effects. Here we report that pharmacological preconditioning with low-dose GYKI imparts a significant protection against KA-induced seizures in vivo. GYKI (3 mg/kg, s.c.), 90 to 180 min. prior to high-dose KA, markedly reduced seizure scores, virtually abolished all level 3 and level 4 seizures, and completely suppressed KA-induced hippocampal cFOS expression. In addition, preconditioned animals exhibited significant reductions in high frequency/high amplitude spiking and ECoG power in the delta, theta, alpha and beta bands during KA. Adverse behaviours often associated with higher doses of GYKI were not evident during preconditioning. The fact that GYKI is effective at doses well-below, and at pre-administration intervals well-beyond previous studies, suggests that a classical blockade of ionotropic AMPA receptors does not underlie anticonvulsant effects. Low-dose GYKI preconditioning may represent a novel, prophylactic strategy for neuroprotection in a field almost completely devoid of effective pharmaceuticals.